Triple-Negative Breast Cancer Cells Recruit Neutrophils by Secreting TGF-β and CXCR2 Ligands - SenGupta, Shuvasree; Hein, Lauren E.; Xu, Yang; Zhang, Jason; Konwerski, Jamie R.; Li, Ye; Johnson, Craig; Cai, Dawen; Smith, Janet L.; Parent, Carole A. (Frontiers in Immunology, 2021)
Tumor associated neutrophils (TANs) are frequently detected in triple-negative breast cancer (TNBC). Recent studies also reveal the importance of neutrophils in promoting tumor progression and metastasis during breast cancer. However, the mechanisms regulating neutrophil trafficking to breast tumors are less clear. We sought to determine whether neutrophil trafficking to breast tumors is determined directly by the malignant potential of cancer cells. We found that tumor conditioned media (TCM) harvested from highly aggressive, metastatic TNBC cells induced a polarized morphology and robust neutrophil migration, while TCM derived from poorly aggressive estrogen receptor positive (ER+) breast cancer cells had no activity. In a three-dimensional (3D) type-I collagen matrix, neutrophils migrated toward TCM from aggressive breast cancer cells with increased velocity and directionality. Moreover, in a neutrophil-tumor spheroid co-culture system, neutrophils migrated with increased directionality towards spheroids generated from TNBC cells compared to ER+ cells. Based on these findings, we next sought to characterize the active factors secreted by TNBC cell lines. We found that TCM-induced neutrophil migration is dependent on tumor-derived chemokines, and screening TCM elution fractions based on their ability to induce polarized neutrophil morphology revealed the molecular weight of the active factors to be around 12 kDa. TCM from TNBC cell lines contained copious amounts of GRO (CXCL1/2/3) chemokines and TGF-β cytokines compared to ER+ cell-derived TCM. TCM activity was inhibited by simultaneously blocking receptors specific to GRO chemokines and TGF-β, while the activity remained intact in the presence of either single receptor inhibitor. Together, our findings establish a direct link between the malignant potential of breast cancer cells and their ability to induce neutrophil migration. Our study also uncovers a novel coordinated function of TGF-β and GRO chemokines responsible for guiding neutrophil trafficking to the breast tumor.